The anti-inflammatory activity of resveratrol in acute kidney injury: a systematic review and meta‐analysis of animal studies - Shangmei Cao; Xiuhong Fu; Shaozhe Yang; Shuifu Tang (Taylor & Francis Group, 2022)
Context Accumulated experimental evidence suggests that resveratrol (RSV) may have an effect on acute kidney injury (AKI) by inhibiting inflammation. However, the credibility of the evidence for this practice is unclear.Objective This study investigated the effect of RSV on AKI and the underlying mechanism.Methods We searched PubMed, EMBASE, and Web of Science from 2005 to April 2022 for controlled animal trials assessing the effect of conventional resveratrol versus placebo on renal function outcome after AKI. This study was registered within the International Prospective Register of Systematic Reviews (PROSPERO) as number CRD42022329596.Results We retrieved 455 studies, 25 studies comprising data of 436 animals that met the inclusion criteria. Our meta-analysis suggested that RSV treatment was significantly associated with lower levels of serum creatinine (Scr) and blood urea nitrogen (BUN). The greatest effects were recorded in low-dose (<20 mg/kg/day) groups rather than in high-dose (> 20 mg/kg/day) groups. For time-response effects, subgroup analysis indicated that intervention duration of RSV can influence the treatment effect, and more beneficial effects were observed when studies had a drug administration time of <2 weeks.Discussion and conclusions This systematic review of animal AKI studies showed a consistently favourable effect of RSV as compared to placebo on renal function outcomes that increased with lower TNF-α, IL-6, and IL-1β. RSV has a more beneficial effect on SA-AKI animal models than the others. When the RSV intervention dose was low (< 20 mg/kg/day) and the intervention time was <2 weeks, more benefits could be observed.